SHARIA ECONOMIC LAW POLICY UMAR IBN AL-KHATTAB - Muh Said; Syafi'ah Syafi'ah; Ade Jamarudin (Tadayun: Jurnal Hukum Ekonomi Syariah, 2023)
Umar Ibn al-Khattab (584-644 M) was the second caliph in Islamic history after replacing the caliph Abu Bakr al-Siddiq. He was one of the companions of the Prophet SAW who had strong morals, was energetic, fair, and wise, had a firm and complex character, and had managerial and administrative abilities. Umar as caliph, only ruled for more than ten years, but in that short period, there were many successes and advancements experienced by Islamic society, especially in the economic field. So it is prevalent in the history of the Islamic world that the reign of Umar was a golden age in Islamic history. The success of Umar's leadership, especially in reforming and developing the community's economic system and prospering their lives, is due to scientific abilities, ijtihad, and a well-established managerial system in regulating the country's foreign exchange. Utilization and proper distribution, as well as rigorous and disciplined supervision. This can be understood from the various economic law policies carried out when applying the principles of production, consumption, and distribution based on fairness in law enforcement and fair distribution. Abstrak Umar Ibn al-Khattab (584-644 M) sebagai khalifah kedua dalam sejarah Islam setelah menggantikan khalifah Abu Bakar al-Shiddiq. Ia adalah salah seorang sahabat Nabi saw yang memiliki moral kuat, energik, adil dan bijaksana, memiliki karakter yang tegas dan keras, serta kemampuan manajerial dan administratif. Umar sebagai khalifah, hanya memerintah selama 10 tahun lebih, akan tetapi dalam periode yang singkat banyak keberhasilan dan kemajuan yang di alami masyarakat Islam, terutama di bidang ekonomi. Sehingga sangat populer dalam sejarah dunia Islam bahwa masa pemerintahan Umar merupakan abad keemasan dalam sejarah Islam. Keberhasilan kepemimpinan Umar khususnya dalam mereformasi dan mengembangkan sistem perekonomian masyarakat sekaligus mensejahterakan kehidupan mereka, karena berkat kemampuan keilmuan, ijtihadi dan sistem manajerial yang mapan dalam mengatur devisa Negara. Pemanfaatan dan pendistribusian yang tepat serta pengawasannya yang sangat ketat dan disiplin. Hal tersebut, dapat dipahami dari berbagai kebijakan hukum ekonomi yang dilakukan ketika menerapkan prinsip-prinsip produksi, konsumsi dan distribusi, dengan dasar adil dalam penegakan hukum, dan adil dalam pendistribusian.